Prognostic and Predictive Effect ofTP53Mutations in Patients with Non–Small Cell Lung Cancer from Adjuvant Cisplatin–Based Therapy Randomized Trials: A LACE‐Bio Pooled Analysis. Issue 6 (June 2016) - Ma, Xiaoli; Le Teuff, Gwénaël; Lacas, Benjamin; Tsao, Ming Sound; Graziano, Stephen; Pignon, Jean‐Pierre; Douillard, Jean‐Yves; Le Chevalier, Thierry; Seymour, Lesley; Filipits, Martin; Pirker, Robert; Jänne, Pasi A.; et al.
ABSTRACT : Introduction: : Tumor protein p53 gene ( TP53 ) mutations are common in stage I through III non–small cell lung cancer, but clinical trials have shown inconsistent results regarding their relationship to the effects of adjuvant therapy. The objective is to clarify their putative prognostic and predictive effects. Methods: : A pooled analysis of TP53 mutations (exons 5–8) was conducted in four randomized trials (the International Adjuvant Lung Cancer Trial, J BRonchus 10, Cancer and Leukemia Group B‐9633, and Adjuvant Navelbine International Trialist Association trial) of platinum‐based adjuvant chemotherapy (ACT) versus observation (OBS). Hazard ratios (HRs) and 95% confidence intervals (CIs) of mutant versus wild‐type (WT) TP53 for overall survival (OS) and disease‐free survival (DFS) were estimated using a multivariable Cox model stratified on trial and adjusted on sex, age, and clinicopathological variables. Predictive value was evaluated with an interaction between treatment and TP53 . Results: : A total of 1209 patients (median follow‐up 5.5 years) were included. There were 573 deaths (47%) and 653 DFS events (54%). Mutations (434 [36%]) had no prognostic effect (OBS HROS = 0.99, 95% CI: 0.77–1.28, p = 0.95; HRDFS = 0.99, 95% CI: 0.78–1.25, p = 0.92) but were marginally predictive of benefit from ACT for OS (test for interaction: OS, p = 0.06; DFS, p = 0.11). Patients with WT TP53 had a tendency toward better outcomes with ACT than did those in the OBS group (HROS = 0.77, 95% CI: 0.62–0.95, p = 0.02; HRDFS = 0.75, 95% CI: 0.62–0.92, p = 0.005). In the ACT arm, a deleterious effect of mutant versus WT TP53 was observed (HROS = 1.40, 95% CI: 1.10–1.78, p = 0.006; HRDFS = 1.31, 95% CI: 1.04–1.64, p = 0.02). Conclusions: : TP53 mutation had no prognostic effect but was marginally predictive for survival from ACT. In patients who received ACT, TP53 mutation tended to be associated with shorter survival than wild‐type TP53 .